2004
DOI: 10.1073/pnas.0308177101
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective organocatalytic construction of pyrroloindolines by a cascade addition–cyclization strategy: Synthesis of (–)-flustramine B

Abstract: Pyrroloindoline and bispyrroloindoline are a subclass of alkaloid structural motifs that commonly exhibit biological activity. An enantioselective organocatalytic approach to the synthesis of pyrroloindoline architecture is described. The addition-cyclization of tryptamines with ␣,␤-unsaturated aldehydes in the presence of imidazolidinone catalysts 1 and 8 provides pyrroloindoline adducts in high yield and excellent enantioselectivities. This transformation is successful for a wide range of tryptamine and ␣,␤-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
117
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 442 publications
(123 citation statements)
references
References 65 publications
0
117
0
6
Order By: Relevance
“…8 In 2004, MacMillan et al reported the enantioselective synthesis of (-)-flustramine B, using 6-bromotryptamine and acrolein as starting materials, and compound 2 as organocatalyst, by a cascade addition-cyclization strategy (Scheme 1). 9 More recently, the same research group used imidazolidinone 2 for aldehyde-aldehyde aldol reactions obtaining as major compound the enantiomer of the most favored product in the proline catalyzed process. 10 List and coworkers have also obtained good yields and enantioselectivities in asymmetric hydrogenations of α,β-unsaturated aldehydes using amine 2 as organocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…8 In 2004, MacMillan et al reported the enantioselective synthesis of (-)-flustramine B, using 6-bromotryptamine and acrolein as starting materials, and compound 2 as organocatalyst, by a cascade addition-cyclization strategy (Scheme 1). 9 More recently, the same research group used imidazolidinone 2 for aldehyde-aldehyde aldol reactions obtaining as major compound the enantiomer of the most favored product in the proline catalyzed process. 10 List and coworkers have also obtained good yields and enantioselectivities in asymmetric hydrogenations of α,β-unsaturated aldehydes using amine 2 as organocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, all of the newly isolated flustramines described here exhibited levorotation. Although we only report the relative configuration for the novel flustramines, it is worth noting that enantioselective syntheses of derivatives of flustramine B 16,17,24 and flustramine A 24 have consistently shown levorotatory species having an absolute configuration equivalent to that shown for 1-10, 12, and 13, although the R and S designations vary with the types of substituents at C-3a and N-8.…”
Section: Flustra Alkaloids From the Bryozoan Flustra Foliaceamentioning
confidence: 99%
“…15 The later synthesis of ent-debromoflustramine B established the configuration of natural flustramine B as being 3aS,8 a R. 16 More recently, Austin et al reported the synthesis of chiral flustramine B identical to the natural product using a cascade addition-cyclization approach. 17 Other studies have targeted racemic debromodihydroflustramine C, 18,19 racemic flustramine C, 20 various racemic flustramines, 21 racemic dihydroflustramine C and flustramine E, 22 racemic flustramines A and C, 23 and scalemic flustramines A and B. 24 We report here studies building on our previous work with F. foliacea collected from Canadian waters.…”
mentioning
confidence: 99%
“…[2] Not surprisingly, the majority of studies in this field have been focused on the Friedel-Crafts reaction of indoles with a range of electrophiles. [3] Indeed, even C3-substituted indoles demonstrate high nucleophilicity; [4] C3-selective reactions have been realized by means of electrophilic compounds and subsequent tandem addition to the newly formed imine group. This processes lead to the construction of fused indolines having C3-quaternary stereocenters.…”
mentioning
confidence: 99%